Predictors of Warfarin Time in Therapeutic Range after Continuous‐Flow Left Ventricular Assist Device. Issue 10 (7th October 2019) - Henderson, James B.; Iyer, Prashanth; Coniglio, Amanda C.; Katz, Jason N.; Chien, Christopher; Hollis, Ian B.
Abstract : Introduction: Patients with a continuous‐flow left ventricular assist device (CF‐LVAD) require anticoagulation with a vitamin K antagonist to prevent thromboembolic events. Fluctuations in the international normalized ratio are associated with both increased thrombotic and bleeding episodes. To date, risk factors for low time in therapeutic range (TTR) among ambulatory patients with a CF‐LVAD have not been explored. Methods: A retrospective single‐center analysis of 121 patients implanted with a CF‐LVAD was performed. International normalized ratios were systematically recorded from the initial postdischarge outpatient visit to 12 months of time on the device. Risk factors for low TTR were evaluated using a multivariable linear regression analysis. Each of the 21 independent variables was entered into a stepwise regression designed to minimize the Akaike information criteria. Results: In the multivariable analysis, the model output revealed that every 1‐year increase in age was associated with a 0.4% increase in TTR (p=0.008), and every 1 mile further from clinic was associated with a 0.08% increase in TTR (p=0.03). Female sex was associated with a 10.1% decrease in TTR (p=0.04), type 2 diabetes was associated with an 11.5% decrease in TTR (p=0.006), and prior warfarin use was associated with an 8.3% decrease in TTR (p=0.03). Conclusion: In CF‐LVAD recipients receiving warfarin, increasing age and distance from clinic are independent predictors of higher TTR. Female sex, type 2 diabetes, and prior warfarin use are independent predictors of lower TTR.